48.5k views
2 votes
Begin with the series solution y-?~anz" to derive the recursive relation (n +2)(n +1)an+ -an-2, n2 2 for the differential equation y+2y0 and write out the first six non-zero terms.

1 Answer

7 votes

I guess the ODE is supposed to be


y''+2y=0

So if


y=\displaystyle\sum_(n\ge0)a_nz^n\implies y''=\sum_(n\ge0)(n+2)(n+1)a_(n+2)z^n

then


\displaystyle\sum_(n\ge0)(n+2)(n+1)a_(n+2)z^n+2\sum_(n\ge0)a_nz^n=0


\displaystyle\sum_(n\ge0)\bigg[(n+2)(n+1)a_(n+2)+2a_n\bigg]z^n=0

so that


(n+2)(n+1)a_(n+2)+2a_n=0

for
n\ge0, or equivalently,


n(n-1)a_n+2a_(n-2)=0\implies a_n=-\frac2{n(n-1)}a_(n-2)

for
n\ge2. Note the dependency between every other coefficient - this means we can consider two cases:

  • If
    n=2k, where
    k\ge0 is an integer, then


k=0\implies n=0\implies a_0=a_0


k=1\implies n=2\implies a_2=-\frac2{2\cdot1}a_0


k=2\implies n=4\implies a_4=-\frac2{4\cdot3}a_2=((-2)^2)/(4!)a_0


k=3\implies n=6\implies a_6=-\frac2{6\cdot5}a_4=((-2)^3)/(6!)a_1

and so on, with


a_(2k)=((-2)^k)/((2k)!)a_0

  • If
    n=2k+1, then


k=0\implies n=1\implies a_1=a_1


k=1\implies n=3\implies a_3=-\frac2{3\cdot2}a_1


k=2\implies n=5\implies a_5=-\frac2{5\cdot4}a_3=((-2)^2)/(5!)a_1

and so on, with


a_(2k+1)=((-2)^k)/((2k+1)!)a_1

Then the ODE has solution


\displaystyle y(x)=\sum_(k\ge0)(a_(2k)z^(2k)+a_(2k+1)z^(2k+1))

and the first six non-zero terms occur for
0\le n\le5, for which we get


\boxed{a_0\left(1-x^2+\frac{x^4}6\right)+a_1\left(x-\frac{x^3}3\right)}

User Cardern
by
6.2k points